The Effectiveness of Morrison’s Model in Acquiring Concepts Among Eighth-Grade Female Students in National and Civic Education Courses - AlTous, Dania Ali Mahmoud; Al-Kilani , Ahmed Mohieddin (Dirasat: Educational Sciences, 2023)
Objective :This study aims to demonstrate the effectiveness of the developed Morrison's Model in acquiring concepts among eighth-grade students in the national and civic education course. Methods: The study adopted the semi-experimental approach. The sample of the study consisted of 60 female students from Noor Al-Qabas Model School of Directorate of Education for Russeifa in the 2021/2022 academic year. The students were divided into two groups: control and experimental, each comprising 30 female students. To achieve the study's objectives, a teaching plan was prepared based on the developed Morrison's Model, and an objective test to assess concept acquisition was developed, consisting of 30 multiple-choice questions. Results: The results demonstrated statistically significant differences at the significance level of (α = 0.05) in concept acquisition for the experimental group that studied using the developed Morrison Model. Conclusions: The employment of the developed Morrison Model in teaching national and civic courses resulted in significant improvements in concept acquisition among eighth-grade female students.